2017
DOI: 10.18632/oncotarget.20351
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and risk of lung cancer: a meta-analysis of prospective cohort studies

Abstract: BackgroundStudies exploring the association between chronic obstructive pulmonary disease (COPD) and lung cancer have yielded mixed results. We conducted a meta-analysis of the published prospective cohort studies to have a clear understanding about this association.MethodsWe searched the MEDLINE and EMBASE databases from inception to December 31, 2016. Bibliographies were also reviewed for additional information. Random-effects model was used to calculate summary relative risk (SRR) and corresponding 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
4
11
1
Order By: Relevance
“…5 A history of tuberculosis, chronic bronchitis, emphysema, or asthma bronchiectasis and a family history of lung cancer are risk factors for lung cancer, as confirmed by research. [9][10][11][12] This study found that people with these characteristics had better LDCT screening compliance. From a clinical perspective, pulmonary tuberculosis, chronic bronchitis, Downloaded From: https://jamanetwork.com/ on 11/06/2020 emphysema, and asthma bronchiectasis usually require LDCT to confirm the diagnosis, and clinicians recommend that these high-risk populations be regularly reviewed for LDCT.…”
Section: Discussionmentioning
confidence: 60%
“…5 A history of tuberculosis, chronic bronchitis, emphysema, or asthma bronchiectasis and a family history of lung cancer are risk factors for lung cancer, as confirmed by research. [9][10][11][12] This study found that people with these characteristics had better LDCT screening compliance. From a clinical perspective, pulmonary tuberculosis, chronic bronchitis, Downloaded From: https://jamanetwork.com/ on 11/06/2020 emphysema, and asthma bronchiectasis usually require LDCT to confirm the diagnosis, and clinicians recommend that these high-risk populations be regularly reviewed for LDCT.…”
Section: Discussionmentioning
confidence: 60%
“…Smoking plays an important role in lung cancer and COPD [38, 39]. Numerous studies have shown that the longer smoking time and the greater amount of smoking can cause the greater probability of developing lung cancer and the higher mortality rate of lung cancer [4042]. Smoking can cause inflammation and oxidative stress in the lungs, which can trigger COPD and lung cancer [43].…”
Section: Chronic Inflammation In Different Types Of Cancersmentioning
confidence: 99%
“…Infections increase the incidence of several malignancies (e.g., Human papillomavirus types 6 and 11 DNA sequences in cervical cancers, Helicobacter pylori infection in colorectal carcinoma) . Lung cancer often evolves in damaged lungs (e.g., COPD, emphysema, IPF) . In these lung diseases, mucociliary abnormality can grant mutagens from the smoke or further air pollution longer contact period at these locations, promoting the progress of pulmonary malignancy formation .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced disease, older age and comorbidities often make histological verification difficult and may also be associated with less favorable treatment options . Lung cancer often develops in damaged lungs (e.g., chronic obstructive lung disease, emphysema, idiopathic pulmonary fibrosis [IPF]) and underlying lung diseases might make diagnosis and treatment even more difficult . In addition to lung disease, numerous factors can additionally predispose lung cancer patients to develop lower respiratory tract infection (LRTI), including damage to anatomical barriers during invasive procedures .…”
Section: Introductionmentioning
confidence: 99%